Distribution patterns of hepatitis B surface antigen (HBsAg) in the liver of hepatitis patients. - Ray, M B (1976)
One hundred liver biopsies from 100 hepatitis patients were examined by the indirect immunofluorescent technique for the detection of HBsAg. Of the 60 positive specimens 52 were diagnosed as various types of chronic hepatitis and 8 were acute hepatitis. Four main distribution patterns of HBsAg were obtained: full cytoplasmic fluorescence with diffuse lobular distribution; cytoplasmic fluorescence with spotty distribution; peripheral fluorescence in the cell membrane and/or cell peripheries; and focal cytoplasmic positivity. There was an inverse relationship between the number of positive hepatocytes and the extent of liver cell necrosis. The distribution patterns of HBsAg were distinctive in each type of chronic hepatitis and in acute hepatitis. Homogeneous full cytoplasmic fluorescence, distributed diffusely in the whole liver lobule, was observed in chronic persistent hepatitis and in cirrhosis with little activity whereas peripheral liver cell membrane and/or peripheral cytoplasmic fluorescence associated with cytoplasmic positivity in a smaller number of hepatocytes was a characteristic finding in chronic aggressive hepatitis, active cirrhosis, and acute hepatitis with possible transition to chronicity. Focal cytoplasmic fluorescence was observed in acute hepatitis and a group of biopsies in chronic hepatitis in which HBsAg was detected in the liver but no antigen was detectable in the serum. The results show that the different patterns of distribution of HBsAg in the liver biopsy are helpful for the histological diagnosis of different types of HBAg positive viral hepatitis and are consistent with the hypothesis of the role of specific immune response in the pathogenesis of type B viral hepatitis.